Morphological characterization of bell pepper (Capsicum annuum var. grossum) genotypes and their application for distinctness, uniformity and stability testing - SOOD, SONIA; SOOD, RUCHI; VIDYASAGAR, VIDYASAGAR (The Indian Journal of Agricultural Sciences, 2011)
A study was carried out during 2004–05 on morphological characterization of bell pepper (Capsicum annuum L. var. grossum Sendt.) and to establish distinctness of the candidate variety from all other varieties. A total of 25 lines of bell pepper were grouped for several agromorphological descriptors. All the genotypes were intermediate/compact in growth habit except genotype ‘Mid Way’ (prostate) and ‘SKAU-SP 614’, ‘SKAU-SP 609’, ‘SKAU-SP 633-1’, ‘SKAUSP 609-1’, ‘Rajer collection’, ‘EC 464107’ and ‘EC 464115’ (erect). Wide diversity (31 to 70 cm) has been observed in plant height. All the genotypes have erect flower position except ‘SKAU-SP 633-1’, ‘Kandaghat selection’ (intermediate) and ‘Rajer collection’ (pendent). The blocky fruit shape, which is most desirable for Indian market was observed in genotypes ‘Nishat 1’, ‘SKAU-SP 614’, ‘SKAU-SP 616-1’, ‘SKAU-SP 633-1’, ‘SKAU-SP 82-1’, ‘SKAU-SP 648’, ‘SKAU-SP 601’, ‘SKAU-SP 609-1’, ‘Capsicum 143570’, ‘HC 201’, ‘Kandaghat selection’, ‘EC 464107’, ‘UHF 494’, ‘California Wonder’, ‘Mid Way’, ‘Local Belgam’, ‘EC 464119’ and ‘EC 464115’. Almost all the varieties are in green group for fruit colour except ‘Russian Yellow’ and ‘EC 464115’ which are in yellow group.